Cancer Incidence and Mortality Estimates in 2022 in Southeast Asia: A Comparative Analysis - Dee, Edward Christopher (Archīum Ateneo, 2025)
Background Cancer is a leading cause of morbidity and mortality in southeast Asia. We aimed to present and interpret cancer incidence and mortality statistics in the 11 constituent countries of Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, Philippines, Singapore, Thailand, Timor-Leste, and Viet Nam to inform research priorities, health services, and cancer policy. Methods The number of new incident cases and deaths for all cancers combined and for leading cancers were extracted from the GLOBOCAN 2022 database developed by the International Agency for Research on Cancer for the 11 countries in southeast Asia. For comparison, we extracted estimates from China, India, Japan, Pakistan, South Korea, and the USA. We estimated age-standardised incidence rates (ASIRs) and age-standardised mortality rates (ASMRs) per 100 000 person-years; projections to 2050 were also estimated by multiplying ASIR and ASMR estimates for 2022 by the expected population for 2050. Data on race or ethnicity were not collected. Findings Data were extracted on Dec 5, 2024. For the 11 countries in southeast Asia for all cancers combined, 545 725 (47·6%) of a total of 1 146 810 incident cases were estimated in men and 601 085 (52·4%) incident cases were estimated in women in 2022. In the same period, 385 430 (53·8%) of a total of 716 116 deaths were estimated in men and 330 686 (46·2%) deaths were estimated in women. The total cancer ASIR in men and women was highest in Singapore (235·89 per 100 000 and 231·01 per 100 000 respectively), while the corresponding ASMR was greatest in Laos for men (132·91 per 100 000) and Brunei for women (104·20 per 100 000). Breast cancer was the most common cancer among women in all countries (highest ASIRs in Singapore [72·61 per 100 000] and the Philippines [60·34 per 100 000]), and the most common cause of cancer mortality among women in the Philippines (ASMR 21·47 per 100 000), Malaysia (19·30 per 100 000), Singapore (17·82 per 100 000), Viet Nam (14·67 per 100 000), Indonesia (14·35 per 100 000), and Timor-Leste (10·24 per 100 000). Among men, lung cancer was the most frequently diagnosed cancer in the Philippines (ASIR 37·66 per 100 000), Malaysia (23·23 per 100 000), Myanmar (21·59 per 100 000), and Indonesia (21·30 per 100 000), and the leading cause of death due to cancer in the Philippines (ASMR 33·59 per 100 000), Singapore (31·94 per 100 000), Brunei (23·84 per 100 000), Malaysia (20·42 per 100 000), Myanmar (19·91 per 100 000), Indonesia (18·96 per 100 000), and Timor-Leste (12·95 per 100 000). Liver cancer contributed the greatest incidence and mortality in men in Cambodia, Laos, Viet Nam, and Thailand, and was also the leading cause of death due to cancer among women in Laos (ASMR 13·49 per 100 000), Cambodia (13·34 per 100 000), and Thailand (12·14 per 100 000). Cervical cancer was the leading cause of death due to cancer in women in Myanmar (ASMR 13·37 per 100 000); colorectal cancer was the most common cancer in men in Singapore (ASIR 39·41 per 100 00) and Brunei (37·70 per 100 000). By 2050, 2·03 million new cases of cancer are anticipated in southeast Asia annually, an 89·2% increase in men and a 65·6% increase in women, relative to 2022. Interpretation The current patterns of cancer incidence and mortality in southeast Asia are primarily driven by breast cancer in women and lung cancer in men, but infection-related cancers (liver and cervix) are common in some countries. Regional collaborations must be strengthened to improve cancer prevention, diagnosis, care, and research in southeast Asia. Funding National Cancer Institute and the Prostate Cancer Foundation.